29.1k views
0 votes
Simplify −5(x−8)+7(x+3)=x+11

User Uwe Hafner
by
4.4k points

1 Answer

3 votes

Answer:

If you're solving for x, the answer is -50. x = -50

Explanation:

Remove the parenthesis and distribute:

-5(x-8) + 7(x+3) = x + 11

-5x + 40* + 7(x+3) = x + 11

-5x + 40 +7x + 21* = x + 11

Collect like terms and calculate:

| -5x + 7x

2x + 40 + 21 = x + 11

| 40 + 21

2x + 61 = x + 11

Move them to the other side like so:

2x - x* + 61 = 11

| -61

2x - x = 11 - 61

Combine:

x = 11 - 61

x = -50

User Iamkdblue
by
5.0k points